2013
DOI: 10.3329/bjvm.v9i2.13456
|View full text |Cite
|
Sign up to set email alerts
|

Udder-Halve-Wise Comparative Prevalence of Clinical and Sub-Clinical Mastitis in Lactating Goats With Their Bacterial Pathogens and Antibiotic Sensitivity Patterns in Bangladesh

Abstract: Goats are the major parts of subsidiary economy of the rural people in Bangladesh. Dairy animals including lactating goats are prone to the intramammary infection (IMI) and associated with a lot of economic impact on the farmers but the reports on caprine mastitis are very limited in inland literature. This study was undertaken to determine the udder-halve-wise comparative prevalence of clinical and sub-clinical caprine mastitis with their associated bacterial pathogens and antibiotic sensitivity patterns duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
4
12
3
Order By: Relevance
“…Earlier, the highest prevalence of Coagulase Negative Staphylococci (CNS) was reported by Gelasakis et al (2016), Nickerson et al (2015) and Silanikove et al (2014). Other than single infection (85%), mixed infections (15%) were also found in this study which was supported by the observation of Sarker and Samad (2011). They reported that both the clinical and sub-clinical mastitis affected udder-halves had single (clinical 76.27% and sub-clinical 71.43%) and mixed (clinical 16.95% and sub-clinical 24.49%) bacterial infections.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Earlier, the highest prevalence of Coagulase Negative Staphylococci (CNS) was reported by Gelasakis et al (2016), Nickerson et al (2015) and Silanikove et al (2014). Other than single infection (85%), mixed infections (15%) were also found in this study which was supported by the observation of Sarker and Samad (2011). They reported that both the clinical and sub-clinical mastitis affected udder-halves had single (clinical 76.27% and sub-clinical 71.43%) and mixed (clinical 16.95% and sub-clinical 24.49%) bacterial infections.…”
Section: Discussionsupporting
confidence: 88%
“…The subclinical and clinical or acute and chronic mastitis were mostly prevalent (Raikwar and Shukla, 2015). In clinical mastitis redness, swelling, heat, and pain were present, while the sub-clinical mastitis rarely manifest any evidence of inflammation except reducing milk yield (Sarker and Samad, 2011). Subclinical mastitis is the most common in goats and is mainly caused by contagious bacteria (Persson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli are known as the most common environmental contaminants because these are found as a normal flora in the intestine of almost all farm animals (Ansari et al, 2014;Begum et al, 2014). From above workers, Sarker and Samad (2011) reported the incidence of Escherichia coli as a second most in subclinical mastitis milk samples, however in the present study we observed the Bacillus subtilis as second most prevalent organism. These variations might be due to differences in geographical location and/or management conditions at the farm (Abel et al, 2014).…”
Section: Prevalence and Incidence Of Bacterial Species In Subclinicalcontrasting
confidence: 55%
“…The prevalence of subclinical mastitis in different herds was recorded between 15-79%. Sarker and Samad (2011) recorded the prevalence of subclinical mastitis in black Bengal goats and reported a significantly higher incidence in left udder halves (79.66 %) as compared to the right udder halves (20.34%). Whereas in present study the prevalence was recorded higher (52.63%) in right quarters as compared to left side quarters (47.36%).…”
Section: Prevalence Of Subclinical Mastitis In Dairy Goats Analysed Bmentioning
confidence: 99%
“…The lower immunity level of periparturient cows makes the cow more prone to infection in the udder (Rainard and Riollet, 2006). Once a cow gets infected or diseased during the periparturient period, it becomes more susceptible to udder infection due to lowered immunity (Sarker and Samad, 2011;Sharma et al, 2007). Calcium ions are necessary for muscle constriction.…”
Section: Conditionmentioning
confidence: 99%